Cloth Face Coverings: Effect of Decontamination Method on Fabric Performance. Issue 1 (January 2023) - Goodge, Katarina; Frey, Margaret
Various textiles have previously been evaluated for use in cloth face masks as a reusable option to help control the spread of respiratory viruses, but only their initial performance was tested. In this study, a broad range of fabrics (3 knit, 7 woven, and 3 nonwoven) were characterized for filtration efficiency (FE) and air permeability (AP) before and after 40 decontamination cycles by home laundry, microwave-generated steam, or dishwasher sterilization. AP was quantified following ASTM D737, and FE was assessed using NaCl aerosol in a simulated breathing system. While most fabrics maintained or improved their FE after 40 decontamination cycles, the AP of many fabrics decreased due to detergent buildup, fiber breakage, and fabric shrinkage. Tightly woven cotton fabrics had unacceptably low AP and FE performance. Knit and nonwoven structures had the best balance of properties, and although they are not recommended for use in single-layer masks, they have potential use in multilayer masks.